Wide Temperature All‐Solid‐State Ti3C2Tx Quantum Dots/L‐Ti3C2Tx Fiber Supercapacitor with High Capacitance and Excellent Flexibility - Juan He; Fuquan Ma; Wenpu Xu; Xuexia He; Qi Li; Jie Sun; Ruibin Jiang; Zhibin Lei; Zong‐Huai Liu (Advanced Science, 2024)
Abstract Ti3C2Tx Quantum dots (QDs)/L‐Ti3C2Tx fiber electrode (Q3M7) with high capacitance and excellent flexibility is prepared by a wet spinning method. The assembled units Ti3C2Tx nanosheets (NSs) with large size (denoted as L‐Ti3C2Tx) is obtained by natural sedimentation screen raw Ti3AlC2, etching, and mechanical delamination. The pillar agent Ti3C2Tx QDs is fabricated by an ultrasound method. Q3M7 fiber electrode gave a specific capacitance of 1560 F cm−3, with a capacity retention rate of 79% at 20 A cm−3, and excellent mechanical strength of 130 Mpa. A wide temperature all‐solid‐state the delaminated montmorillonite (F‐MMT)/Polyvinyl alcohol (PVA) dimethyl sulfoxide (DMSO) flexible hydrogel (DHGE) (F‐MMT/PVA DHGE) Q3M7 fiber supercapacitor is assembled by using Q3M7 fiber as electrodes and F‐MMT/PVA DHGE as electrolyte and separator. It showed a volume specific capacitance of 413 F cm−3 at 0.5 A cm−3, a capacity retention of 97% after 10 000 cycles, an energy density of 36.7 mWh cm−3 at a power density of 311 mW cm−3, and impressive capacitance and flexibility over a wide temperature range of −40 to 60 °C. This work provides an effective strategy for designing and assembling wide temperature all‐solid‐state fiber supercapacitors with optimal balance of capacitive performance and flexibility.